FAKE NEWS VERSUS CORPORATE REPUTATION: TECHNIQUES TO PROTECT BRANDS: Received: 20th July 2021; Revised: 25th October 2021, 31st January 2022, 26th March 2022; Accepted: 28th March 2022 - Adriani, Roberto (PEOPLE: International Journal of Social Sciences, 2022)
This paper aims to investigate how companies can protect their reputation against fake news, also giving some examples. The literature indicates that not only can individual companies or brands be victims of fake news, but also - and perhaps more frequently - entire industries. The pharmaceutical industry illustrates this as it was already the subject of conspiracy theories, which then exploded during the Covid-19 pandemic. The literature seems to suggest two basic points. The first one is that fake news, including deep fakes, is a serious threat to corporate reputation and entire industrial sectors, as it is capable of inflicting considerable damage, including financial. However, companies are making constant progress in developing and refining techniques to monitor and combat fake news. From this point of view, it is also noted that if technology can help on the one hand to create misinformation, on the other hand, it is valid to support the fight against fake news. It can also be seen that single companies are usually more capable of reacting than industrial sectors, like pharmaceuticals which have been attacked by fake news and conspiracy theories for a long time.